2017
DOI: 10.1371/journal.pone.0188641
|View full text |Cite
|
Sign up to set email alerts
|

Dual expression of immunoreactive estrogen receptor β and p53 is a potential predictor of regional lymph node metastasis and postoperative recurrence in endometrial endometrioid carcinoma

Abstract: Although histological grade and muscular invasion are related to the malignant behaviors of endometrial endometrioid carcinoma, lymphatic and/or distant metastases are unexpectedly encountered, even in patients in the low-risk group. To re-evaluate additional reliable parameters to predict the risk of progression, we examined the immunohistochemical expression profiles of p53 and estrogen receptor (ER) β proteins. Patients with endometrial endometrioid carcinoma who underwent surgical treatment at our hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 38 publications
4
19
0
Order By: Relevance
“…The p53-positive rate is 17–45% in all histological types of endometrial carcinomas. In type-I endometrial cancer, the p53-positive rate was 10–44%, whereas a high rate of p53 expression was observed in 30–86% of type-II endometrial cancer [59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75] (Table 1). Overexpression of p53 is a poor prognostic factor in both type-I and type-II endometrial cancer.…”
Section: Significance Of P53 In Gynecologic Cancersmentioning
confidence: 99%
“…The p53-positive rate is 17–45% in all histological types of endometrial carcinomas. In type-I endometrial cancer, the p53-positive rate was 10–44%, whereas a high rate of p53 expression was observed in 30–86% of type-II endometrial cancer [59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75] (Table 1). Overexpression of p53 is a poor prognostic factor in both type-I and type-II endometrial cancer.…”
Section: Significance Of P53 In Gynecologic Cancersmentioning
confidence: 99%
“…In a previous study, we were able to show, that expression of ERβ was even sufficient to significantly inhibit proliferation of hormone-independent COS-1 cells and to increase apoptosis even in the absence of E2 [30]. However, the role of this receptor in endometrial cancer is still controversial, as some studies reported downregulation of ERβ in endometrial cancer [79], and others observed increased expression of this receptor in endometrial tumor tissue or its association with disease progression [1012]. Concordant studies on other cancer entities demonstrated that ERβ expression is decreased or lost in a variety of tumors when compared to normal tissue, a fact that was reported to have negative consequences on survival or therapy of different cancer entities [31–35].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to endometrial cancer, the role of this receptor is still controversial. Whereas various studies report downregulation of ERβ in endometrial cancer [79], others observed increased expression of this receptor in endometrial tumor tissue or its association with disease progression [1012]. From other hormone dependent tissues like the breast, ERβ is known to exert inhibitory effects on proliferation and invasion, both dependent and independent from presence of ERα [1315].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, some studies have demonstrated ERβ positivity to be correlated with a more aggressive clinical outcome15 and with the proliferation marker, Ki-67 43–45. ERβ has also been identified as a novel activator of wild-type p53-dependent transcription, which leads to poorer survival of luminal breast cancer cells 42 46–50…”
Section: Discussionmentioning
confidence: 99%